Clinical characteristics and mortality predictors of patients with cancer hospitalized by COVID-19 in a pediatric third-level referral center - Hernández-Regino, Laura-Monserrat; De Jesús Castillejos-López, Manuel; Aquino-Gálvez, Arnoldo; Velasco-Hidalgo, Liliana; García-Guzmán, Alda; Aguilar-Ortiz, Marco; Cárdenas-Cardos, Rocío; Torres-Espíndola, Luz María (Frontiers in Pediatrics, 2022)
Abstract Background: More than 135 million COVID-19 cases (coronavirus disease 2019) have been reported worldwide until today, with over 2.9 million deaths. Several studies have demonstrated that disease severity is lower in the pediatric population compared to adults; however, differences are described in patients with chronic diseases, including oncological patients. Current world literature suggests patients with comorbidities, among them cancer patients, have an increased risk of unfortunate outcomes. Therefore, we aimed to describe the clinic and epidemiologic characteristics, and mortality associated factors of a cancer pediatric patients cohort hospitalized for COVID-19. Methods: A retrospective, descriptive study of the cases of patients with cancer hospitalized for COVID-19. A total of 40 pediatric included for the analysis. Data on pediatric with COVID-19 including clinical and epidemiological records, laboratory, imaging studies, COVID-19 diagnostic method, and medical treatment. Results: Of 40 pediatric admitted with cancer with a confirmed diagnosis of COVID-19, 42.5% were solid tumors, 40% leukemias, 17.5% lymphomas. The clinical parameters associated with mortality were stage IV tumor (p=0.029), intubation (p<0.001). The biochemical factors associated lower survival were platelet count under 25,000 cells/mm3 (p<0.001), D-dimer over 1 µg/ml (p=0.003), clinical malnutrition (p=0.023) and disseminated intravascular coagulation (p=0.03). Conclusions: Our findings showed that the fever was the most frequent symptom, the clinical parameters associated with mortality were stage IV tumor, intubation, saturation percentage, RDW, platelets, creatinine, ALT, D-dimer, ferritin, and FiO2 percentage. The platelet count, D-dimer, nutritional status, and disseminated intravascular coagulation were significantly associated with lower survival.